Sleep restriction induced energy, methylation and lipogenesis metabolic switches in rat liver. (December 2017) - Sengupta, Arjun; Rhoades, Seth D.; Kim, Eun Ji; Nayak, Soumyashant; Grant, Gregory R.; Meerlo, Peter; Weljie, Aalim M.
Abstract: Sleep curtailment is ubiquitous in modern day society. Sleep debt is associated with maladaptive physiological changes that can lead to cardiometabolic and neuropsychiatric pathologies. Recent literature has shown the effects of sleep restriction (SR) on systemic metabolic profiles in biofluids, implying that tissue-specific metabolomes are impacted by SR. To test this hypothesis, we assessed hepatic metabolic profiles of rats after 5 days of SR using UPLC–MS based metabolomics analysis and gene expression analysis. Our data suggests distinctive effects of SR on the liver metabolic profile of rats compared to forced-activity control animals. We observed specific impacts of SR on NAD metabolism through NAD accumulation and upregulation of Nampt, the rate determining step of NAD salvage. Additional multi-omic changes were observed in methionine metabolism, with an elevated SAM:SAH ratio under SR. This effect on one carbon metabolism is indicative of increased methylation potential. Changes in TCA cycle intermediates and ATP-citrate lyase ( Acly) gene expression were observed that may be related to altered circulatory lipid profiles previously reported documenting the chrono-metabolic connection. Taken together with previous investigations, these observations are consistent with a model of decreased TCA activity with concomitant increase in lipogenesis induced by SR. These tissue-specific mechanistic insights into metabolic effects of SR provide a springboard to future metabolic intervention studies.